Traditional Chinese medicines and capecitabine‐based chemotherapy for colorectal cancer treatment: A meta‐analysis - Hui‐Zhong Jiang; Ya‐Li Jiang; Bing Yang; Feng‐Xi Long; Zhu Yang; Dong‐Xin Tang (Cancer Medicine, 2023)
Abstract This meta‐analysis was conducted to evaluate the efficacy and safety of the addition of Traditional Chinese Medicine (TCMs) to capecitabine‐based regimens for colorectal cancer (CRC) in term of tumor. The eight electronic databases including Cochrane Library, PubMed, Web of Science (WOS), Excerpt Medica Database (Embase), Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Journals (CQVIP), and Wanfang Database were systematically searched for eligible studies from their inception to March 2021. Thirty‐nine randomized controlled trials were involved in this study, and all the data were analyzed by Review Manager 5.3 (Nordic Cochran Centre, Copenhagen, Denmark) and R 4.0.5 software. The meta‐analyses suggested that TCMs in combination with capecitabine‐based regimens increased objective response rate (ORR) in the palliative treatment of CRC (risk ratio [RR], 1.35 [1.17, 1.55], I2 = 0%), disease control rate (DCR) (RR, 1.22 [1.12, 1.32], I2 = 3%), and quality of life (QOL) (RR, 1.71 [1.44, 2.03], I2 = 0%), with decreased risks of myelosuppression, anemia, thrombocytopenia, liver/renal dysfunction, neurotoxicity, nausea/vomiting, neutropenia, diarrhea, leukopenia, improved the peripheral lymphocyte, reduced the expression of tumor markers, and related factors. Further sensitivity analysis of specific plant‐based TCMs found that dangshen, fuling, and gancao had significantly higher contributions to the results of the RR. The results show that capecitabine‐based chemotherapy combined with TCM in the treatment of CRC increases the efficiency of ORR and DCR, reduces chemotherapeutic agents‐associated adverse reactions, and improves their life quality as compared with chemotherapy alone, but further randomized and large sample of studies are needed.